1954
DOI: 10.1063/1.1721631
|View full text |Cite
|
Sign up to set email alerts
|

16 Percent Aluminum-Iron Alloy Cold Rolled in the Order-Disorder Temperature Range

Abstract: The methods of fabricating 16 percent Al-Fe from cast slab to thin-gauge sheet are described in some detail. The melting, casting, homogenizing, hot rolling, and cold rolling at 575°C and room temperature are described. Particular attention is focused upon the 575°C cold rolling from the standpoint of the possible beneficial effects derived from an ordering reaction which occurs in this alloy. The technique of cold reduction from 0.007 in. to 0.0005 in. at room temperature is discussed. Magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Developments of Fe-Al-based alloys in the United States can be traced back to at least the early 1950s, when alloy series termed Alfenol and Thermenol were developed at the Naval Ordnance Laboratory (13)(14)(15)(16), Ferral at the Ford Motor Company (17)(18)(19), DB-2 at The Martin Company (20,21), and Fe-Cr-Al at the Batelle Memorial Institute (22). Prototype duct halves and jet engine compressor blades were forged from these alloys, and furnace hearths, heat-treat boxes, and turbine exhaust cones were welded (13,15,16,23,24).…”
Section: Historical Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Developments of Fe-Al-based alloys in the United States can be traced back to at least the early 1950s, when alloy series termed Alfenol and Thermenol were developed at the Naval Ordnance Laboratory (13)(14)(15)(16), Ferral at the Ford Motor Company (17)(18)(19), DB-2 at The Martin Company (20,21), and Fe-Cr-Al at the Batelle Memorial Institute (22). Prototype duct halves and jet engine compressor blades were forged from these alloys, and furnace hearths, heat-treat boxes, and turbine exhaust cones were welded (13,15,16,23,24).…”
Section: Historical Remarksmentioning
confidence: 99%
“…Whether the improved ductility of this alloy is due to internal stresses is not clear, as local X-ray diffraction investigations yielded no clear evidence. It has been frequently demonstrated that deformation processing can also improve ductility (14,34,(127)(128)(129)(130), although it is not clear whether, e.g., grain refinement or an increased number of mobile dislocations is responsible (123). Figure 7 includes examples of the improvement in ductility after rolling, forging, or additive manufacturing.…”
Section: Ductilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Process approaches that appear promising include growth texturing in an as-cast structure and the preferential recrystallization of thin sheets. Deformation texturing methods of interest, based on success in texturing of Fe-Si and Fe-Al alloys, include extrusion, forging and rolling [Nachman 1954, Kad 1997, Novikov 1997. A final potential texturing process includes the use of an aligning magnetic field in conjunction with powder metallurgy.…”
Section: Polycrystalline Preparation and Performancementioning
confidence: 99%